Mesozoic magmatic evolution of the Laiyuan complex: Tracing the crust-mantle and lithosphere-asthenosphere interactions in the central North China Craton - Xue, Fei; Santosh, M.; Tsunogae, Toshiaki; Yang, Fan; Tan, Hongbing; Chen, Guohui; Li, Chao; Xu, Yunchou (Frontiers in Earth Science, 2023)
The Laiyuan complex in the central North China Craton (NCC) incorporating different magmatic suites offers an excellent opportunity to investigate the lithospheric evolution and cratonic destruction. However, the petrogenesis and tectonic implications of this magmatic suite remain debated due to lack of integrated studies. Here we evaluate the magmatism and tectonic setting assembling data from multidisciplinary investigations of the Laiyuan complex. The complex is composed of volcanic suites, granitoids, ultramafic-mafic intrusions, and dykes showing common features of enrichments in LREEs and LILEs and depletions in HFSEs. Detailed petrogenetic considerations suggest that crust-mantle and lithosphere-asthenosphere interactions contributed to the formation of various magmatic suites. The involvement of thickened lower crust and enriched lithospheric mantle in the source, and diverse magmatic processes including partial melting, fractional crystallization, and magma mixing have played a significant role in the petrogenesis of the Laiyuan complex. Furthermore, the lithosphere-asthenosphere interaction induced by thinning lithosphere and upwelling asthenosphere controlled the source variations from dolerites to lamprophyres. The complex formed in an extensional tectonic setting triggered by the subduction of the Paleo-Pacific Plate. The subduction, rollback, and stagnation of the Paleo-Pacific slab contributed to the modification of the lithospheric architecture of the NCC. A slow and gradual thermal-mechanical erosion occurred at the central NCC whereas the rapid and intense lithospheric delamination occurred at the eastern NCC contributing to different lithospheric evolution. Both of the mechanisms combined with the subduction of Paleo-Pacific slab played a significant role in the destruction of the NCC and the formation of various magmatic suites. An integrated model is proposed to describe the magmatic evolution of the Laiyuan complex. During Jurassic, the subduction of the Paleo-Pacific Plate reached beneath the central NCC. At 145-140 Ma, the fast slab rollback occurred and lead to hot asthenosphere upwelling and extensional setting in the central NCC inducing the crust-mantle interaction accounting for the petrogenesis for the formation of granitoids with MMEs (137-126 Ma), volcanic rocks (131-127 Ma), and felsic dykes (131-127 Ma). Through time, the lithosphere became substantially thin with the asthenospheric input increasing to form dolerite dykes at 125-117 Ma and lamprophyre dykes at 115-111 Ma.